Neurodevelopmental phenotype caused by a de novo PTPN4 single nucleotide variant disrupting protein localization in neuronal dendritic spines. Issue 6 (11th October 2018) - Szczałuba, Krzysztof; Chmielewska, Joanna J.; Sokolowska, Olga; Rydzanicz, Małgorzata; Szymańska, Krystyna; Feleszko, Wojciech; Włodarski, Paweł; Biernacka, Anna; Murcia Pienkowski, Victor; Walczak, Anna; Bargeł, Elżbieta; Królewczyk, Katarzyna; et al.
Abstract : Protein tyrosine phosphatase non‐receptor type 4 ( PTPN4 ) encodes non‐receptor protein tyrosine phosphatase implicated in synaptic plasticity and innate immune response. The only report of PTPN4 ‐associated disease described a neurodevelopmental disorder associated with a whole gene deletion. We describe a child with developmental delay, autistic features, hypotonia, increased immunoglobulin E and dental problems with a novel mosaic de novo variant in PTPN4 (hg19 chr2:g.120620188 T > C, NM_002830.3:p.[Leu72Ser]/c.215T>C) located in domain that controls protein subcellular distribution. Studies in mouse hippocampal neurons transfected with non‐mutated or mutated human PTPN4 showed that despite their similar expression in neurons the mutated protein was absent from dendritic spines. Next, we studied patient's primary blood mononuclear cells' response to lipopolysaccharide stimulation and found no difference from control in phosphorylation of TBK1 and IRF3 (involved in Toll‐like receptor 4 signaling) and induction of cytokines' messenger RNA. We conclude that the PTPN4 p.(Leu72Ser) variant is a likely cause of neurodevelopmental symptoms of our proband whereas its role in immune dysfunction requires further studies. Abstract :